Endangered economies : how the neglect of nature threatens our prosperity - Heal, G. M. (Columbia University Press, 2017)
In the decades since Geoffrey Heal began his field-defining work in environmental economics, one central question has animated his research: "Can we save our environment and grow our economy'" This issue has become only more urgent in recent years with the threat of climate change, the accelerating loss of ecosystems, and the rapid industrialization of the developing world. Reflecting on a lifetime of experience not only as a leading voice in the field, but as a green entrepreneur, activist, and advisor to governments and global organizations, Heal clearly and passionately demonstrates that the only way to achieve long-term economic growth is to protect our environment. Writing both to those conversant in economics and to those encountering these ideas for the first time, Heal begins with familiar concepts, like the tragedy of the commons and unregulated pollution, to demonstrate the underlying tensions that have compromised our planet, damaging and in many cases devastating our natural world. Such destruction has dire consequences not only for us and the environment but also for businesses, which often vastly underestimate their reliance on unpriced natural benefits like pollination, the water cycle, marine and forest ecosystems, and more. After painting a stark and unsettling picture of our current quandary, Heal outlines simple solutions that have already proven effective in conserving nature and boosting economic growth. In order to ensure a prosperous future for humanity, we must understand how environment and economy interact and how they can work in harmony-lest we permanently harm both.